First record of Marphysa chirigota (Annelida: Eunicidae) in the Mediterranean Sea (Gulf of Tunis) - CHAIBI, MARWA; ROMANO, CHIARA; AZZOUNA, ATF; MARTIN, DANIEL (Mediterranean Marine Science, 2021)
To date, the genus Marphysa is represented by only three species, Marphysa sanguinea, Marphysa aegypti and Marphysa birgeri in the Mediterranean Sea. Combining morphological, molecular data (16S rRNA and cytochrome c oxidase subunit I mitochondrial loci) and environmental information, we are here presenting the first Mediterranean report of Marphysa chirigota, based on the specimens collected at Radès Station (Gulf of Tunis, western Mediterranean). The current information on the distribution of of the Marphysa species strongly supports that M. sanguinea inhabits hard bottoms and has a restricted distribution close to its type location (south English coast and nearby NE European Atlantic). The specimens from Radès Station, as well as all those reported as M. sanguinea along the Tunisian coast, were found in the shallow water soft bottoms. Therefore, we suggest that the presence of M. sanguinea in Tunisia seems is doubtful, and all Marphysa species reports from Tunisia might correspond to M. chirigota.